2015
DOI: 10.1371/journal.pone.0121571
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spartina alterniflora Invasion on Soil Respiration in the Yangtze River Estuary, China

Abstract: Many studies have found that plant invasion can enhance soil organic carbon (SOC) pools, by increasing net primary production (NPP) and/or decreased soil respiration. While most studies have focused on C input, little attention has been paid to plant invasion effects on soil respiration, especially in wetland ecosystems. Our study examined the effects of Spartina alterniflora invasion on soil respiration and C dynamics in the Yangtze River estuary. The estuary was originally occupied by two native plant specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 64 publications
0
12
0
1
Order By: Relevance
“…Compared with the native plants of Suaeda salsa , the Spartina invasion increases the soil organic carbon (SOC) content by 27.0%-69.6%, and increases ecosystem primary productivity and carbon sequestration capacity significantly [35]. But Bu et al indicated that Spartina invasion does not change SOC significantly [36]. The Spartina invasion increases carbon reserves in the rhizosphere soil of reed wetland [37].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the native plants of Suaeda salsa , the Spartina invasion increases the soil organic carbon (SOC) content by 27.0%-69.6%, and increases ecosystem primary productivity and carbon sequestration capacity significantly [35]. But Bu et al indicated that Spartina invasion does not change SOC significantly [36]. The Spartina invasion increases carbon reserves in the rhizosphere soil of reed wetland [37].…”
Section: Discussionmentioning
confidence: 99%
“…After its initial appearance on the Chongming Island located in the Yangtze River estuary in mid-1990′s, it has replaced native Phragmites australis and Scirpus mariqueter and becomes a dominant plant species there 11 . S. alterniflora invasion changes soil microorganism community 14 15 and stimulates greenhouse gas fluxes 16 . S. alterniflora invasion also increases soil C and N pool sizes 17 .…”
mentioning
confidence: 99%
“…Error bars in SRR indicate the mean ± 1 SD from triplicate cores. labile organic compounds (i.e., DOC) (Bu et al, 2015;Cheng et al, 2008;Zhang et al, 2017), which fuel anaerobic respiration in the sediment (Hines et al, 1989;Hines, 1991;Kostka et al, 2002a;Koretsky et al, 2008). Indeed, depth-integrated (0-20 cm) DOC concentrations at SA (560 mmol m −2 ) were 2.2 times and 2.9 times higher than that measured at SJ (258 mmol m −2 ) and UMF (192 mmol m −2 ), respectively ( Table 2).…”
Section: Influence Of Invasive S Anglica On C Org Oxidationmentioning
confidence: 94%
“…Previous studies have reported that invasion of Spartina species remarkably altered sedimentary biogeochemical cycles (Liao et al, 2007;Cheng et al, 2008;Zhang et al, 2017;Wang et al, 2019), physico-chemical properties of sediment Bu et al, 2015;Zhang et al, 2019), and microbial communities in sediments associated with nitrification and denitrification (Dollhopf et al, 2005;Zhang et al, 2013;Gao et al, 2019), sulfur-oxidizing and reducing processes (Thomas et al, 2014;Cui et al, 2017) and CH 4 emissions (Yuan et al, 2016). However, little is known about the impact of these invading salt marsh plants on biogeochemical processes and associated microbial communities in the Ganghwa intertidal flats of the Han River estuary in the Yellow Sea.…”
Section: Introductionmentioning
confidence: 99%